What is masculinity in a contemporary Australian context? - Steven Litherland; Peter Miller; Shannon Hyder (Journal of Men's Health)
Background: Social norms around gender have been rapidly changing around the world. As a psychological variable, “masculinity” may be at a “critical juncture” in Australia where old definitions are now open to challenge and where new and more useful definitions may be necessary. Methods: The present exploratory study investigated the meaning(s) of masculinity in a contemporary setting with data derived from semi-structured interviews with 39 adult Australian citizens or permanent residents for whom issues of masculinity likely resonated. The present study employed a qualitative methodology with thematic analysis used to examine contemporary accounts of masculinity among 39 participants (18 males, 15 females and 6 non-binary) aged between 21 and 74 years (Mean Age = 36.1 years, Standard Deviation = 17.18) and recruited from a large capital city of Melbourne and a regional city of Geelong. Results: Thematic analysis identified three broad themes, namely (1) “Physical and Performative”, whereby physicality was important in contemporary versions of what is masculine, with masculinity also typically deemed a performance or persona; (2) “Prosocial Masculinity”, in that it now incorporates mostly positive attributes; and (3) Is “Evolving” from old stereotypes usually seen as dysfunctional to attributes now viewed as essentially human qualities. Conclusions: The present findings suggest there exists a “myriad of masculinities” that are largely performative with characteristics once labelled as “masculine” no longer viewed as gendered phenomena. For some interviewees, the label of masculinity is outdated, playing little to no role in their lives. The concept of masculinity in Australia, or at least in this sample, appears in transition, with the present findings suggesting that it is indeed at a “critical juncture” with new meanings emerging and where new and more useful concepts may need to be considered.